VDC_100102371237.0X000001. Issue 10 (October 2018) - Gray, Kelsey; Ayabe, Reed; Shover, Andrew; Moazzez, Ashkan; Ozao-Choy, Junko; Dauphine, Christine
The rate of positive margins after breast conserving surgery (BCS) can be as high as 50 per cent, and optimal techniques for reducing rates of positive margins are presently debated. Our institution has previously demonstrated low rates of margin re-excision using a standardized approach to intraoperative selective margin excision for patients undergoing BCS. We hypothesized that this approach can be used for patients with ductal carcinoma in situ (DCIS) and can yield similar rates when compared with invasive cancer. We performed a retrospective analysis of women with breast cancer who underwent BCS from January 2012 through July 2016 using our institution's standardized approach to selective margin resection. Of the 152 patients who underwent BCS, there were 30 (20%) with DCIS and 122 (80%) with invasive cancer. There was no statistically significant difference in re-excision rates for DCIS (13.3%) and invasive cancer (13.1%). Notably, the DCIS group had a larger mean lesion size ( P = 0.00009); however, the lesion was visible on ultrasound more often in the invasive cancer group ( P = 0.007). This standardized approach to intraoperative selective margin excision can produce similar rates of margin re-excision for DCIS and invasive cancer and may be a viable option for lowering re-excision rates for patients with DCIS.